The Influence of Corporate Governance on Intellectual Capital Disclosure: Evidence from Bank on Indonesian Stock Exchange 2015-2019 - Slamet; Indrayati; Erlin Melani (The Institute of Academic Research and Publication (IARP), 2021)
The purpose of this study was to examine the effect of Corporate Governance on Intellectual Capital Disclosure. The sample used in this study consisted of 22 banking companies listed on the Indonesia Stock Exchange in 2015-2019. The data used is in the form of an annual report. The sampling technique in this study was to use purposive sampling. This study uses multiple regression analysis. The statistical analysis results show that partially the audit committee and external auditor variables have a significant positive effect on intellectual capital disclosure. Meanwhile, the independent commissioner variable has no significant effect on intellectual capital disclosure. The ownership concentration variable harms intellectual capital disclosure. Simultaneously, the variables of the independent commissioner, ownership concentration, audit committee, and external auditor have a significant effect on intellectual capital disclosure.